Renal Dysfunction in a Cohort of Renal Transplant Recipients: Impact of BK Polyomavirus. (4th October 2017) - Borges, Álvaro H; Cozzi-Lepri, Alessandro; Hirsch, Hans H; Cunha-Bang, Caspar Da; Wareham, Neval Ete; Frederiksen, Casper Møller; Mocroft, Amanda; Lundgren, Jens; Sørensen, Søren Schwartz; ,
Abstract: Background: BK Polyomavirus (BKPyV) causes renal allograft dysfunction and premature graft loss. We investigated the relationship between BKPyV viremia and renal dysfunction among renal transplant recipients enrolled in MATCH, a large transplantation cohort from Rigshospitalet, Copenhagen. Methods: We included renal transplant recipients after October 1, 2011. Patients with primary graft nonfunction were excluded. BKPyV DNA was tested for screening in blood 60, 90, 179, and 270-day post-transplant. Cox models with baseline covariates were used to identify factors independently associated with a composite endpoint of eGFR <40, confirmed 25% eGFR decrease, graft loss, or death. For analyses of renal function, baseline was defined as the time of first BKPyV test. Separate models assessed factors associated with BK viremia, investigating recipient- and donor-related factors, induction immunosuppressive therapy, and rejection as covariates (Figure). Baseline was defined as 42d post transplantation to allow renal function stabilization. Results: In total, 322 patients were included. Eighty-seven had BK viremia. Ninety-eight developed the composite endpoint (1 developed eGFR <40, 95 a confirmed 25% eGFR decrease [6 of whom died and 2 lost the graft], and 2 died). Annual incidence of BK viremia was stable over the study period ranging from 33.0 to 33.6 /100 PYFU ( P = 0.98). Factors independently associated with detection of BK viremia were antibody-mediated rejection (adjusted hazards ratio [aHR], 95% CI: 2.68, 0.97–7.39, P = 0.057) and immunoglobulin(IVIG)-based treatment for rejection (3.20, 0.99–10.42, P = 0.053). Participants with BK viremia had a higher risk of developing the composite endpoint (2.06, 1.25–3.39, P = 0.005) (figure). Other factors independently associated with the composite endpoint were use of Rituximab + IVIG + Basiliximab during induction (2.66, 1.29-5-49, vs. Basiliximab, P = 0.008) and donor age (1.19, 1.00–1.43 per 10 year older, P = 0.05). Conclusion: Early detection of BK viremia was associated with a higher risk of renal dysfunction, graft loss and death in our cohort. Antibody-mediated rejection and immunoglobulin-based treatment for rejection appeared to increase the risk of BK viremia. Disclosures: Á. H. Borges, Lundbeckfonden: Grant recipient (R219-2016–762), Grant recipient and Research grant